High-throughput sequence analysis of Ciona intestinalis SL trans-spliced mRNAs: Alternative expression modes and gene function correlates - Matsumoto, Jun; Dewar, Ken; Wasserscheid, Jessica; Wiley, Graham B.; Macmil, Simone L.; Roe, Bruce A.; Zeller, Robert W.; Satou, Yutaka; Hastings, Kenneth E.M.

(untitled) (Genome Research, 2010)
Pre-mRNA 5′ spliced-leader (SL) trans-splicing occurs in some metazoan groups but not in others. Genome-wide characterization of the trans-spliced mRNA subpopulation has not yet been reported for any metazoan. We carried out a high-throughput analysis of the SL trans-spliced mRNA population of the ascidian tunicate Ciona intestinalis by 454 Life Sciences (Roche) pyrosequencing of SL-PCR-amplified random-primed reverse transcripts of tailbud embryo RNA. We obtained ∼250,000 high-quality reads corresponding to 8790 genes, ∼58% of the Ciona total gene number. The great depth of this data revealed new aspects of trans-splicing, including the existence of a significant class of “infrequently trans-spliced” genes, accounting for ∼28% of represented genes, that generate largely non-trans-spliced mRNAs, but also produce trans-spliced mRNAs, in part through alternative promoter use. Thus, the conventional qualitative dichotomy of trans-spliced versus non-trans-spliced genes should be supplanted by a more accurate quantitative view recognizing frequently and infrequently trans-spliced gene categories. Our data include reads representing ∼80% of Ciona frequently trans-spliced genes. Our analysis also revealed significant use of closely spaced alternative trans-splice acceptor sites which further underscores the mechanistic similarity of cis- and trans-splicing and indicates that the prevalence of ±3-nt alternative splicing events at tandem acceptor sites, NAGNAG, is driven by spliceosomal mechanisms, and not nonsense-mediated decay, or selection at the protein level. The breadth of gene representation data enabled us to find new correlations between trans-splicing status and gene function, namely the overrepresentation in the frequently trans-spliced gene class of genes associated with plasma/endomembrane system, Ca2+ homeostasis, and actin cytoskeleton.